Bats of Central Ukraine: a Synopsis - Godlevska, L.; Rebrov, S.; Vorobei, P.; Savchenko, M.; Panchenko, P. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2022)
Here, we represent the first review of the bat fauna of the large territory of Central Ukraine (to the west from Dnieper River). The review is based on results of the original survey in 1999–2021 and data from all available sources (publications, museum collections). Fauna of the region includes 24 bat species: Eptesicus, 2 species; Barbastella, 1; Myotis, 10; Nyctalus, 3; Pipistrellus, 4; Plecotus, 2; Vespertilio, 1; Rhinolophus, 1. For each species there is a short description of its distribution (illustrated by a map), used roosts, seasonality of presence and reproductive status within the study area. The bat fauna composition is analysed by three distinguished subregions, from north to south: of mixed forests, the forest-steppe, and the Dniester river. The estimation of prevalence and comparative abundance of the species in the region is given. The general review of bat roosts, by their types (under- and overground), seasonality of usage, and sheltered species is presented. The paper is supplemented with the extensive array of original, earlier unpublished, primary data on bat records in the region.